Microwave modulated transdermal drug delivery using chitosan nanocarrier / Asif Nawaz - Nawaz, Asif (Institute of Graduate Studies, UiTM, 2017)
The chitosan has been used as the primary excipient in transdermal particulate dosage form design. This study investigated the transdermal drug delivery profiles and mechanisms of chitosan nanoparticles and their cellular uptake mechanisms by melanoma cells as a function of nanoparticles attributes and pre-treatment effects of skin by microwave. Low molecular weight chitosan of smaller size, higher zeta potential and degree of deacetylation were obtained via microwave ligation of polymer chains at solution state. Low molecular weight chitosan nanoparticles, loaded with free or conjugated 5-fluorouracil, were prepared by nanospray-drying technique with tween 20 and span 20 as additives. Folate was covalently attached to the chitosan-carboxymethyl 5- fluorouracil conjugate when necessary and subjected to nanoparticulation process. The transdermal drug delivery profiles of chitosan-carboxymethyl 5-fluorouracil nanoparticles across the untreated and microwave-treated skins (2450 MHz 5 min, 5 + 5 min; 3985 MHz 5 min) were examined, against microstructural changes of skin. Both constituent materials of nanoparticles and drug encapsulation were required to succeed the transdermal drug delivery. The drug transport was mediated via nanoparticles carrying the drug across the skin and/or diffusion of the earlier released drug molecules from skin surfaces…